P060 COMBINATION THERAPY WITH TNF-INHIBITORS AND IMMUNOMODULATORS ARE ASSOCIATED WITH SHORTER DURATION TO FIRST SERIOUS INFECTION – THE DEVELOP EXPERIENCE. (7th February 2019) - Gold, Benjamin; Cucchiara, Salvatore; Izanec, James; Busse, Christopher; Wang, Yanli; Escher, Johanna
Abstract: Background: DEVELOP is a multicenter, international, prospective, observational registry of the long-term safety and clinical status of 6070 pediatric patients (pts) with inflammatory bowel disease (IBD) diagnosed prior to 18 years of age who were treated with anti-tumor necrosis factor biologics (aTNF) and/or other medical therapies for IBD. Our aim was to assess the risk factors that lead to first serious infection (SI): an infection requiring hospitalization and/or IV therapy. Methods: Physicians participating in the registry prescribe IBD treatments based on their usual clinical practice and standards of care. Pts are categorized into cohorts according to their IBD medication exposure representing prevalent or incident exposure. The registry started enrollment in 2007 and completed enrollment in 2017. After the initial enrollment visit, data are obtained by the registry physician or designee every 6 months. SI data includes infections that occurred within 91 days of exposure to aTNF relative to non-biologics. The most recent available data cut (June 30 2018) includes 33586 patient years (PY) of follow up in the registry. Results: The analysis of the stepwise Cox regression model for time to first SI among aTNF only pts relative to the non-biologics cohort included 3, 566 Crohn's disease (CD) pts who had at least 1 post-baseline follow-up visit, complete baseline covariate data, and complete disease severity data at event. Covariates that were significantly associated with a shorter duration of time to first SI within 91 days of aTNF exposure (Table 1) included: PCDAI Score (Moderate to Severe vs. Inactive) monotherapy with corticosteroids (CS) combination therapy with aTNF and immunomodulators (IMM), Hospitalization in the year prior to enrollment monotherapy with aTNF, PCDAI Score (Mild vs. Inactive) Female gender Time since IBD was diagnosed The analysis of the stepwise Cox regression model included 1063 ulcerative colitis (UC) pts who also had at least 1 post-baseline follow-up visit, complete baseline covariate data, and complete disease severity data at event. The covariates that were significantly associated with shorter duration of time to first SI (Table 2) included: Monotherapy with CS Monotherapy with aTNF Hospitalization in the year prior to enrollment Partial Mayo Score (Mild vs. Inactive) Combination therapy with aTNF and IMM Conclusion: In CD pts, combination therapy with aTNF/IMM, monotherapy with aTNF or CS, disease severity, recent hospitalization, gender, length of diagnosis and geographic region were all significantly associated with shorter duration of time to first SI. In UC pts, only monotherapy with aTNF or CS, combination therapy with aTNF and IMM, disease severity and recent hospitalization were significantly associated with shorter duration of time to first SI.